Analisis Ekologis Meiofauna Interstisial di Sekitar Pulau Pannikiang, Kabupaten Barru - Muh. Sri, Yusal (bionature, 2011)
Meiofauna were organisms that live in the interstitial. Synonyms were meiobentos. Meiofauna can also be interpreted as a small group of metazoans that sits between microfauna and macrofauna. This was caused by a very small body size and position was hidden in the sediments and did not provide direct benefits to humans (economic benefits). Meiofauna generally known only by scientists who pursue marine biology and ecology. This study aimed to determine the ecological water quality index based on the island of interstitial meiofauna Pannikiang, Barru district. The results showed that the class was the class that dominates the nematode composition and density of meiofauna in Pannikiang Island. Nematodes were very instrumental in the classroom enrich and enhance the productivity of aquatic ecosystems. Based on the ecological value of the index, the index of diversity (H'), Uniformity (E), and dominance (D) showed that P. Pannikiang have good water quality with the diversity of species and the spread of the number of individuals of each species were equal, a unified community and did not find any species that dominate the surrounding waters. Meiofauna ecology index indicates that the water condition in P. Pannikiang not currently experiencing a very severe ecological pressure, meaning that in a stable community structure, environmental conditions is excellent. Therefore, we need public participation and coordination among agencies in the District. Barru to maintain the condition of these waters.